Case Report: Endoscopic trans-cerebellar medullary fissure approach for the management of brainstem hemorrhage - Wang, Xue-Jian; Zhang, Longyao; Yin, Yu-Hua; Wang, Zhi-Feng; Zhang, Yi; Sun, Cheng; Cui, Zhi-Ming (Frontiers in Neurology, 2023)
Objective: The brain stem hematoma (BSH) is of high-risk, and surgery can be deadly and disabling. Recently, endoscopic techniques have been employed for the removal of supratentorial intracerebral hemorrhage, with significant improvement in operative morbidity and mortality compared with other approaches. Here we demonstrate the utility and feasibility of the endoscopic trans-cerebellar medullary fissure approach for the management of brain stem hemorrhage in carefully selected patients. Patients and Methods: Consent was provided by the guardian of the patient before the writing of this report. IRB approval was not necessary as there was no other patient data accessed. A 55-year-old male presented to the emergency department with coma and feeble respiration. CT demonstrated evidence of brain stem hemorrhage. Given the location of the hemorrhage and the desire for early control of an associated developmental obstructive hydrocephalus and feeble respiration, an endoscopic trans-cerebellar medullary fissure approach was chosen as the treatment method. Results: Total resection was achieved and the patient gradually improved post operatively with no new neurologic deficits. He is currently routinely followed up and is conscious with partial hemiplegia. Conclusion: This approach provided direct visualization of the lesion and was minimally invasive. The endoscopic trans-cerebellar medullary fissure approach may be considered as an alternative to open approaches for brain stem hemorrhage in carefully selected patients.